Environmental Social and Governance (ESG) based Mutual Fund Investment in Indonesia - Iramadya Dyah Marjanah; Wardah Yuspin (Proceeding International Conference Restructuring and Transforming Law, 2023)
Investment is a familiar activity in the 4.0 era like today. By utilizing technology that is always developing, Indonesia has become one of the countries that has experienced a significant increase in investment, especially in the capital market. One investment that is growing rapidly is mutual fund investment. Based on the KSEI report, investors in the capital market are dominated by those aged under 30 years, namely 60.32%. Mutual fund investment is an investment that has various advantages. Every investment definitely has risks. Mutual funds are no exception, there are also some risks. Indonesia is a country that has the potential for new renewable energy (EBT), so investing in ESG mutual funds is very suitable in Indonesia. This research uses normative juridical methods. This research uses a qualitative approach. The data used in this research is data originating from literature searches, statutory regulations, and other literature studies. The results of this research areinvestmentThe novelty of this research is that the application of ESG in mutual fund products is quite interesting in terms of paying attention to the surrounding environment. That the regulations regarding investments that adopt the ESG system do not yet have specific regulations governing their implementation. The rule of law is very necessary in order to avoid unwanted fraud. This article tries to provide an alternative to how important ESG-based investment is in Indonesia.